2019
DOI: 10.3390/nu11030512
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF-α Agent Tamarind Kunitz Trypsin Inhibitor Improves Lipid Profile of Wistar Rats Presenting Dyslipidemia and Diet-induced Obesity Regardless of PPAR-γ Induction

Abstract: : The increasing prevalence of obesity and, consequently, chronic inflammation and its complications has increased the search for new treatment methods. The effect of the purified tamarind seed trypsin inhibitor (TTIp) on metabolic alterations in Wistar rats with obesity and dyslipidemia was evaluated. Three groups of animals with obesity and dyslipidemia were formed, consuming a high glycemic index and glycemic load (HGLI) diet, for 10 days: Obese/HGLI diet; Obese/standard diet; Obese/HGLI diet + TTIp (730 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 83 publications
(107 reference statements)
2
25
0
Order By: Relevance
“…Medeiros et al 10 also evaluated the effect of pTTI on plasma CCK and leptin in Wistar rats with diet-induced obesity, and results similar to the partially purified TTI were found 15 , without altering CCK concentrations, but reducing leptin, suggesting an improvement in the leptin resistance profile, a characteristic present in obesity and SM. Further, Carvalho et al 18 indicated pTTI, was able to reduce molecular and plasm levels of TNF-a (tumour necrosis factor-a), VLDL-C (very-low-density lipoprotein-cholesterol), and TG (triglycerides) in Wistar rats with diet-induced dyslipidemia. Thus, we have a protein with beneficial biological effects in experimental studies applied in the context of obesity and associated complications.…”
Section: Introductionmentioning
confidence: 98%
“…Medeiros et al 10 also evaluated the effect of pTTI on plasma CCK and leptin in Wistar rats with diet-induced obesity, and results similar to the partially purified TTI were found 15 , without altering CCK concentrations, but reducing leptin, suggesting an improvement in the leptin resistance profile, a characteristic present in obesity and SM. Further, Carvalho et al 18 indicated pTTI, was able to reduce molecular and plasm levels of TNF-a (tumour necrosis factor-a), VLDL-C (very-low-density lipoprotein-cholesterol), and TG (triglycerides) in Wistar rats with diet-induced dyslipidemia. Thus, we have a protein with beneficial biological effects in experimental studies applied in the context of obesity and associated complications.…”
Section: Introductionmentioning
confidence: 98%
“…Protease inhibitors are proteins that reduced fasting glucose, weight, and inflammation and increased plasma CCK secretion in animal studies [11,12,13,14]. The trypsin inhibitor isolated from tamarind ( Tamarindusindica L.) (TTI) was studied by Carvalho et al [13], proving its satietogenic and anti-inflammatory effect in Wistar rats with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…TTI significantly reduced triglycerides and very low-density lipoproteins (VLDL-c). Mean glucose concentration was lower in the group treated with TTI, although not significantly different from the other groups [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the groups did not show differences in weight gain. pTTI showed great anti-inflammatory potential, reducing the relative expression of TNF-α messenger RNA and positive immunostaining in adipocyte immunohistochemical analysis of obese animals, as well as plasma cytokine concentrations ( 71 ). The anti-inflammatory effects of the isolated or purified inhibitor on adipose tissue were observed regardless of weight changes, which may suggest a direct beneficial effect on this tissue that may alter its structure.…”
Section: Resultsmentioning
confidence: 99%